From Vernacular Wisdom to Passive Design : A Case Study of Joglo Houses in Ngrogung, Ponorogo, Indonesia - Agung Murti Nugroho; Noviani Suryasari; Siti Khomsatun; Fernanda Ayuning Putri (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2026)
Vernacular houses in Indonesia embody indigenous wisdom for climate adaptation, making the performance of their passive design a relevant topic in sustainable architecture. Modernization and increasingly uniform building forms have eroded climate-responsive principles, raising concerns about thermal comfort amid climate change. This study investigates how a Joglo house in Ngrogung, Ponorogo, Indonesia, maintains indoor comfort through passive strategies. Field observations and continuous monitoring over three months measured air temperature and relative humidity in four interior zones (Omah Ngarep, Omah Mburi, Omah Tengah, Kamar). Performance was evaluated using six criteria covering twelve passive-design parameters. The mean indoor temperature stabilized at 25.77 °C (October 26.18 °C; November 25.92 °C; December 25.20 °C), while relative humidity averaged 75.45%, indicating generally comfortable conditions. Comfort gains were chiefly associated with building form and envelope porosity: favorable orientation limiting solar load, insulated roof enclosure, light-colored breathable walls, and jalusi/louvered windows that sustain airflow with supportive site layout. Conversely, underperforming parameters included limited roof volume (29.75% of total), short eaves (60 cm), dark roofing, small operable window area (2.06% of floor area), and low floor elevation (65 cm). Overall, synergistic interactions among orientation, material porosity, and natural ventilation underpin resilient thermal behavior.